Magnetic Resonance Image-Guided Biopsies with a High Detection Rate of Prostate Cancer - Dirk G. Engehausen; Karl Engelhard; Siegfried A. Schwab; Michael Uder; Sven Wach; Bernd Wullich; F. Steffen Krause (The Scientific World Journal)
Aim. To explore the potential of transrectal magnetic resonance image- (MRI-) guided biopsies of the prostate in a patient cohort with prior negative ultrasound guided biopsies. Patients and Methods. Ninety-six men with suspected prostate cancer underwent MRI-guided prostate biopsies under real-time imaging control in supine position. Results. Adenocarcinoma of the prostate was detected in 39 of 96 patients. For individual core biopsies, MRI yielded a sensitivity of 93.0% and a specificity of 94.4%. When stratifying patients according to the free-to-total prostate-specific antigen (PSA) ratio, the prostate cancer discovery rate was significantly higher in the group with ratios less than 0.15 (57.1%). Conclusion. MRI-guided biopsy of the prostate is a diagnostic option for patients with suspected prostate cancer and a history of repeatedly negative transrectal ultrasound-guided biopsies. Combined with the free-to-total PSA ratio, it is a highly effective method for detecting prostate cancer.